Identification of two substrates of FTS_1067 protein - An essential virulence factor of Francisella tularensis - Spidlova, Petra; Senitkova, Iva; Link, Marek; Stulik, Jiri (Acta microbiologica et immunologica Hungarica, 2017)
Francisella tularensis is a highly virulent intracellular pathogen with the capacity to infect a variety of hosts including humans. One of the most important proteins involved in F. tularensis virulence and pathogenesis is the protein DsbA. This protein is annotated as a lipoprotein with disulfide oxidoreductase/isomerase activity. Therefore, its interactions with different substrates, including probable virulence factors, to assist in their proper folding are anticipated. We aimed to use the immunopurification approach to find DsbA (gene locus FTS_1067) interacting partners in F. tularensis subsp. holarctica strain FSC200 and compare the identified substrates with proteins which were found in our previous comparative proteome analysis. As a result of our work two FTS_1067 substrates, D-alanyl-D-alanine carboxypeptidase family protein and HlyD family secretion protein, were identified. Bacterial two-hybrid systems were further used to test their relevance in confirming FTS_1067 protein interactions.
Keywords: bakteriální proteiny; Protein Binding; faktory virulence; Lipoproteins; vazba proteinů; FTS_1067 protein; bacterial two-hybrid assay; Bacterial Proteins; immunopurification; Virulence Factors; Francisella tularensis; lipoproteiny